Clinical Handbook of Insomnia - Attarian, Hrayr P. (Current Clinical Neurology, 2017)
Expanding on the critical contributions of previous editions, this updated and comprehensive resource covers the latest diagnostic criteria of insomnia. The book is thematically divided into two parts. The first section consists of chapters on nomenclature, epidemiology, pathophysiology, diagnosis and differential diagnosis, complications and prognosis and treatment both pharmacological and behavioral. The second features chapters on insomnia in special populations, including ones on children and adolescents, cancer sufferers and survivors, in pregnancy, in menopausal women and in patients with neurological disorders and those with psychiatric illnesses. This third edition fills an important niche in the medical literature by addressing insomnia in its multiple forms, summarizes the findings published in different medical journals, and presents these to the practicing health care provider in an easily accessible format.